Time-motion study in primary health care in moldova: How do family doctors and medical assistants spend their work time? - Altiona Muho; Jari Kempers; Alexandra Topa; Ala Curteanu; Ghenadie Curocichin; Helen Prytherch (PLoS ONE, 2025)
Introduction Despite efforts to strengthen primary health care, Moldova faces continues challenges related to health personnel shortages and distribution disparities, resulting in high workloads. To better understand the current situation, we sought to assess the work-time allocation of family doctors and medical assistants in primary health care centers in Moldova. Methods An observational, cross-sectional study was conducted to investigate health personnel’s time allocated to activity categories, the number and duration of consultations for different health conditions, and the reasons for patient’s visits in nine primary health centers in Moldova. 24 family doctors and 24 medical assistants were observed for five consecutive working days, covering in total 233 workdays and 4,916 consultations. Results Family doctors used 49.2% of their time on direct patient care, 20.4% on administrative tasks and 9.8% on outreach activities. Medical assistants spent 33.6% on administration tasks, 30.9% on direct patient care and 13.6% on outreach activities. Of their direct patient care time, family doctors and medical assistants used 49.8% and 51.7%, respectively, on non-communicable disease consultations. The median duration of doctors’ consultations was 8.55 minutes, whereas medical assistants’ consultations lasted 5.65 minutes. Hypertensive disease and pediatric visits were the most frequent and time-consuming consultations. Health personnel contracted for 1.5 full-time equivalents worked over 10 hours per week shorter than required by their working contracts. Conclusions Family doctors used nearly half of their work time on direct patient care, while medical assistants spent less than one third, with administrative tasks taking up most of medical assistants’ time. Consultation durations were short for both cadres, especially among medical assistants, reflecting the high workload in primary health care in Moldova. Additionally, health personnel contracted for 1.5 full-time equivalents worked consistently fewer hours than required by their contracts, indicating this system does not improve patient access or resolve personnel shortages.